Health care workers' experiences of calling-for-help when taking care of critically ill patients in hospitals in Tanzania and Kenya - Elibariki Godfrey Mkumbo; Tamara Mulenga Willows; Onesmus Odongo Onyango; Karima Khalid; John Maiba; Carl Otto Schell; Jacquie Oliwa; Jacob McKnight; Tim Baker (BMC, 2024)
Abstract Background When caring for critically ill patients, health workers often need to 'call-for-help' to get assistance from colleagues in the hospital. Systems are required to facilitate calling-for-help and enable the timely provision of care for critically ill patients. Evidence around calling-for-help systems is mostly from high income countries and the state of calling-for-help in hospitals in Tanzania and Kenya has not been formally studied. This study aims to describe health workers' experiences about calling-for-help when taking care of critically ill patients in hospitals in Tanzania and Kenya. Methods Ten hospitals across Kenya and Tanzania were visited and in-depth interviews conducted with 30 health workers who had experience of caring for critically ill patients. The interviews were transcribed, translated and the data thematically analyzed. Results The study identified three thematic areas concerning the systems for calling-for-help when taking care of critically ill patients: 1) Calling-for-help structures: there is lack of functioning structures for calling-for-help; 2) Calling-for-help processes: the calling-for-help processes are innovative and improvised; and 3) Calling-for-help outcomes: the help that is provided is not as requested. Conclusion Calling-for-help when taking care of a critically ill patient is a necessary life-saving part of care, but health workers in Tanzanian and Kenyan hospitals experience a range of significant challenges. Hospitals lack functioning structures, processes for calling-for-help are improvised and help that is provided is not as requested. These challenges likely cause delays and decrease the quality of care, potentially resulting in unnecessary mortality and morbidity.